Pulmonary hypertension: Old targets revisited (Statins, PPARs, Beta-Blockers) - Watson,G; Oliver,E; Zhao,L; Wilkins,MR (Handbook of Experimental Pharmacology, 2013)
Pulmonary arterial hypertension is a therapeutic challenge. Despite progress in recent years with three drug classes-prostanoids, endothelin receptor antagonists and phosphodiesterase type 5 inhibitors-long-term patient survival remains poor. Importantly, the introduction and commercial success of these new treatments has been accompanied by growing interest in the pathology of pulmonary hypertension. This, in turn, has stimulated a re-evaluation of the molecular factors driving the structural remodelling of pulmonary arterioles and the opportunities to preserve right ventricular function in pulmonary hypertension. Academics with restricted access to new chemicals have turned to existing drugs to investigate new ideas. It is in this context that the role of statins, peroxisome proliferator-activated receptors (PPARs) and beta-blockers are of interest as potential treatments for pulmonary hypertension. © Springer-Verlag Berlin Heidelberg 2013.